Nitrification processes in groundwaters evidenced by modification on the U contents and 234U/238U activity ratios - Bonotto, D. M. [UNESP] (My University, 1998)
Groundwaters from the Botucatu-Piramboia aquifer system located at the Parana sedimentary basin in Brazil and sampled at Ribeirao Preto city, Sao Paulo State, were chemically and isotopically analyzed, with the aim of evaluating how uranium isotopes 234U and 238U can be utilized to monitor the progress of nitrate, the main indicator of agrichemical pollution into an aquifer. Based on the isotope dilution analysis, the 234U/238U activity ratio and U content data in the groundwaters were utilized to deduce their proportions in a mixture, suggesting that the water not affected significantly by nitrification still dominates the exploitation system involving the studied wells.